Simple constellation shaping for BICM-ID - Qi LI; Lin ZHOU; Bo ZHANG; Bao-ming BAI (Tongxin xuebao)
A novel method of constellation mapping is presented for bit-interleaved coded modulation (BICM) by combining geometry shaping with probabilistic shaping.The transmitted signal points of a practical signal constellation approach the optimal input distribution by exploiting a many-to-one mapping with some signal points unused.With this method,shaping gain can be achieved conveniently with the help of iterative decoding between demodulation and decoder.The optimizations of signal constellation and the mapping from symbols to signal points are performed by the analysis of capacity and the extrinsic information transfer chart.Simulation results show that the proposed constellation mapping outperforms the traditional Gray mapping for BICM with iterative decoding in both AWGN and Rayleigh channels.And the shaping gain achieved can be improved with the increase of the constellation size.